PENGARUH TINGKAT PENDIDIKAN, PENANAMAN MODAL DALAM NEGERI, TINGKAT PARTISIPASI ANGKATAN KERJA DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Dewi Alfatimah; Mike Triani (Universitas Negeri Padang, 2026)
This study comprehensively to analyze the influence of several variables,namely education level, domestic investment (PMDN), labor force participation rate (TPAK), and open unemployment rate (TPT) on economic growth in West Sumatra Province. Secondary data was obtained from the Central Statistics Agency (BPS) covering 19 regencies/cities for the 2020-2024 period. The analysis used panel data-based multiple linear regression with a fixed effects model as the best model. The results show that education level, PMDN, and TPAK have a positive and significant influence on economic growth, while TPT has a negative and significant influence on economic growth. Therefore, the government needs to strengthen policies by improving the quality of education, encouraging productive domestic investment, expanding employment opportunities, and addressing unemployment through job creation to support sustainable economic growth.